ANALYSIS OF HOUSING DEVELOPMENT GROWTH IN DATUK BANDAR TIMUR DISTRICT, TANJUNGBALAI CITY - Lasthreeida Juwita; Abdi Sugiarto; Cut Nuraini (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to analyze the patterns, driving factors, and impacts of housing development growth in Datuk Bandar Timur District, Tanjungbalai City. Using a qualitative approach, this study reveals that housing development in the area shows a rapid spread pattern towards the suburbs with characteristics of cluster and sporadic development. The main driving factors include population growth, local economic development, infrastructure development, changes in people's lifestyles, government policy support, and land availability. This growth has an impact on the environment, society, and infrastructure, such as reduced green open space, changes in social structure, and uneven distribution of public facilities. To overcome these impacts, a sustainable housing development management strategy is needed through spatial planning enforcement, strengthening licensing supervision, environmentally based development, and public education. This research is expected to be the basis for designing more targeted and sustainable housing development policies in the future.